Mississippian Stratigraphic Nomenclature Revisions in Kansas - Franseen, Evan K.; Sawin, Robert S.; Watney, W. Lynn; West, Ronald R.; Layzell, Anthony L.; Ludvigson, Greg A. (Current Research in Earth Sciences, 2018)
This paper reviews proposed Mississippian nomenclature changes in Kansas and outlines the changes to Zeller (1968) that have been adopted by the Kansas Geological Survey. The Sedalia Dolomite is changed to the Sedalia Formation and the Northview Shale is changed to Northview Formation due to lateral lithology changes. The Short Creek Oolite Member as originally defined and described by Smith and Siebenthal (1907) at the type section in Kansas is reinstated. The Cowley Formation as originally defined and described by Lee (1940) in Kansas is reinstated. The Ste. Genevieve Limestone is placed as the basal formation of the Chesteran Stage.